Design and Implementation of a Web GIS Application for Heritage Documentation Using Drones, Lidar, and Laser Scanning: The Case of Lubonja, Korçë, Albania - Leka, Elva; Hoxha, Edmond; Alla, Erland; Pekmezi, Jeton; Qose, Emiliano (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Cultural legacy is an integral part of a country’s identity and its historical and social development. This heritage must be preserved and protected through modern documentation, monitoring, and management technologies. In this context, information and communication technologies (ICT), specifically geographic information systems (GIS), have emerged as transformative tools. Recently, Web GIS applications have expanded opportunities for collaboration and real-time information sharing by offering accessible and interactive platforms for geospatial data integration. Web GIS empowers heritage experts to create precise maps, 3D models, and real-time heritage experts by allowing them to create precise maps, 3D models, and real-time representations of cultural assets. Despite its potential, a significant challenge lies in effectively disseminating information to attract tourists and promote heritage sites. This study explores the application of Web GIS in addressing these challenges in Lubonja, a prehistoric village in Korçë, Albania. It discusses the benefits and limitations of this technology in preserving and promoting cultural heritage and how advanced geospatial technologies can enhance accessibility, public participation, and heritage management.